2021
DOI: 10.1186/s42523-021-00118-z
|View full text |Cite
|
Sign up to set email alerts
|

Microbial composition differs between production systems and is associated with growth performance and carcass quality in pigs

Abstract: Background The role of the microbiome in livestock production has been highlighted in recent research. Currently, little is known about the microbiome's impact across different systems of production in swine, particularly between selection nucleus and commercial populations. In this paper, we investigated fecal microbial composition in nucleus versus commercial systems at different time points. Results We identified microbial OTUs associated with g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 71 publications
(81 reference statements)
1
5
0
Order By: Relevance
“…The total protein and BUN levels are strongly related to the digestion and absorption of protein, particularly the value of BUN, a major end product of protein metabolism in pigs [38,39]. As digestibility increases, fewer substrates are available for intestinal microbial fermentation, hence reducing fecal noxious gas emissions in the environment [40]. This prior research corroborates our finding of reduced BUN and noxious gas levels in weaned piglets.…”
Section: Discussionsupporting
confidence: 87%
“…The total protein and BUN levels are strongly related to the digestion and absorption of protein, particularly the value of BUN, a major end product of protein metabolism in pigs [38,39]. As digestibility increases, fewer substrates are available for intestinal microbial fermentation, hence reducing fecal noxious gas emissions in the environment [40]. This prior research corroborates our finding of reduced BUN and noxious gas levels in weaned piglets.…”
Section: Discussionsupporting
confidence: 87%
“…In pigs, the gut microbiota community is under direct control by the host's genetics, with small to moderate heritabilities (Lu et al, 2018;Bergamaschi et al, 2020a). Maltecca et al (2021) further confirmed this by finding that sires significantly influenced their offspring's gut microbiota composition. In terms of environmental influence, Hildebrand and colleagues (2013) found that the microenvironment accounted for approximately 30% of the variance in mouse gut microbiota and that mice kept in the same cage exhibited similar gut microbiota.…”
Section: Discussionmentioning
confidence: 63%
“…The balanced status of microbes in the intestine, termed as "eubiosis" can be disrupted by several factors including changes in the diet, environment, and invading pathogens [17,18]. Imbalance of the microbes, termed as "dysbiosis" can hamper digestion of feed materials, reduction in the productivity and general host health [19]. Several pathogens can infect a pig's intestinal tract.…”
Section: Discussionmentioning
confidence: 99%